Detecção, quantificação e identificação de bactérias fitopatogenicas isoladas de sementes de trigo - Steilmann, Paula (2014)
The seed sanitary quality deserves attention in the productive systems, recital the negative reflexes that the association of pathogens in seeds can generate. This study aimed to detect, quantify and identify plant pathogenic bacteria present in wheat seeds. Ten different detection methods and quantification of pathogenic bacteria were tested, if using 100, 500, 1000 and 3000 seeds with and without hatching; Centrifugation 3000 and 3000 seeds with seeds with milling. Results showed that the best method for quantification of bacteria in wheat seeds was the one who used 3000 with seed crushing. For those samples containing 100, 500 and 1000 seeds was possible to detect bacteria in different detection methods, but with the number of colony forming units per inferior to the other methods used seed. The results of this test show the importance of the number of seeds in the sample for analysis, as well as the incubation periods. The incidence of seed bacteria was evaluated using the culture media and the medium 523 WBC. It was found that the WBC means the incidence was 92, 82 and 78% respectively for the Quartzo, Marfim and BRS 331 cultivars. Isolates were identified by colony morphology and biochemical and physiological tests. From the tests it was possible to form three distinct groups of isolates due to their characteristics in common. The tests showed that the bacteria isolated from the seeds of wheat belonging to the species Pseudomonas fuscovagine and Xanthomonas translucens. Others belonging to the genus Pseudomonas and Xanthomonas were possible to sort by biochemical methods .